INTEGRATED CONFIGURATION OF FOLDING ROOF-BIPV AND ITS OPTIMATION AT OFFICE BUILDING IN SURABAYA - Susan Susan; I Gusti Ngurah Antaryama; Totok Noerwasito (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2015)
BIPV (Building Integrated Photovoltaics) refers to the application of PV (photo-voltaic) in which the system as well as having the function of producing electricity, also takes the role of building form and element. Empirical facts show that PV in BIPV system is integrated as add-on element only. They didn’t take the role as form giver yet. Electricity output generized by BIPV depends on the amount of solar radiation received by PV panel. There are some factors affect the amount of radiation received. Two of them are tilt and orientation angle of PV panel, and total area prepared for PV panel installment.This research try to rise electricity output by collaborating those two factors with orientation and multiplicity principle in folding concept. Folding element can be arranged based on optimum tilt and orientation angle to reach maximum radiation supply. Also, the collaboration results in bigger surface area to receive higher solar irradiance. Experiment with simulation as it tools will be used as research method to get the optimal configuration of Folding Roof-BIPV.